Spatial Character of Tokyoâ€™s Famous Tourist Attractions - Manifesty, Odilia Renaningtyas (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2019)
Various competitiveness reports on tourism have ranked Japan as one of the most visited countries in Asia. Along with South Korea and Singapore, Japan offers many unique traits to the tourists. Since the establishment of â€œKihinkaiâ€ (lit. Welcome Society), Japanâ€™s first organization to engage with foreign tourists, the country has succeeded in developing various sector of tourism such as heritage sites, nature-based tourism, religious sites, and urban tourism. Tokyo Metropolis, as the capital of Japan, is one of the best examples in urban tourism sector. Hotel occupancy in Tokyo has risen around 80% in the last decade, showing high growth of tourism in the city. The aforementioned growth is supported by many factors, with one of them being the enhancement of tourist attractions. The paper examines Tokyoâ€™s nine most famous tourist attractions specifically at their spatial aspects. The complexity of place, accessibility and the presence of surrounding amenities, as well as the ambience or atmosphere offered by the attractions are the components analyzed to form a set of characteristics that define the character of Tokyoâ€™s tourist attractions. The compiled data can be a precedent study or preliminary guideline for other big cities in Japan or Asia to develop their potential of urban tourism.Â Â Â